2018
DOI: 10.1016/j.arcontrol.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of locomotion efficiency and path-following for underwater snake robots with and without a caudal fin

Abstract: Over the last few decades, the robotics community has shown increasing interest in developing bioinspired swimming robots, driven by the need for more economical, more efficient, autonomous, highly flexible and maneuverable robotic systems for underwater operations. In this paper, we present a bioinspired underwater snake robot (USR) equipped with a passive caudal (tail) fin. In particular, a highly flexible USR configuration is presented that is capable of locomotion both on the ground and underwater due to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…Khalil et al [56], Kelasidi et al [57]- [59], and Pettersen [11] treated the marine snake-like robot as a discontinuous system and made assumptions that the unit is a link and the connection structure is a joint. In these works, the hydrodynamic influence on the link was considered, while the hydrodynamic influence on the joint was ignored.…”
Section: D: Hydrodynamic Characteristicsmentioning
confidence: 99%
“…Khalil et al [56], Kelasidi et al [57]- [59], and Pettersen [11] treated the marine snake-like robot as a discontinuous system and made assumptions that the unit is a link and the connection structure is a joint. In these works, the hydrodynamic influence on the link was considered, while the hydrodynamic influence on the joint was ignored.…”
Section: D: Hydrodynamic Characteristicsmentioning
confidence: 99%
“…Moreover, a fin configuration will not perturb the surroundings as much as the thrusters, which is highly relevant for applications such as archaeological investigation of shipwrecks and non-invasive monitoring of marine life. A comparative study of the robot with and without a caudal fin was presented in Kelasidi et al ( 2017a ). In particular, it was shown that by attaching a passive caudal fin it is possible to double the forward velocity.…”
Section: Setup and Control Systemmentioning
confidence: 99%
“…Substituting the virtual path following control laws designed in equation (21) into the UMV path following error equations (20) and (26)…”
Section: Stability Analysis Of Path Following Errors X E Y Ementioning
confidence: 99%
“…[14][15][16][17][18] In recent years, more and more studies have been conducted on ocean exploration by UMV, and there are many research studies on the path following control of an underactuated UMV for ocean exploration, as path following control system is one the most important control systems for an UMV. [19][20][21][22] Accurate path following control plays an important role for UMV in the oceanic surveys and exploration, an adaptive nonlinear second-order sliding mode controller is proposed to eliminate the chattering motion through a sliding surface during the path following control by Zhang et al, 23 and David et al proposed a novel improved proportional-integral-derivative control approach that enables variable ballast systems on an UMV to complement the underwater vehicle's hydroplanes when altitude keeping over a variable seabed, 24 while subject to complex unknown nonlinearities including un-modeled dynamics, uncertainties, and unknown disturbances, a novel fuzzy uncertainty observerbased path following control scheme for an underactuated marine vehicle is proposed in the study by Wang et al 25 The cooperative path following problem of multiple underactuated UMVs involves two tasks, 26 which may be used to cooperative topographic survey, and the first one is to force each UMV to converge to the desired parameterized path, while the second one is to satisfy the requirement of a cooperative behavior along the paths. A path following control scheme for deep-sea work class remotely operated vehicles subjected to disturbing forces and moments generated by parameter variations, ocean currents, umbilical cables, and other unknown disturbances is designed, 27 while based on a multi-body system concept, a model is designed based on an adaptive controller and a disturbance model is analyzed, which compensates the dynamics of a finite element tether and multi-body underwater vehicle manipulator.…”
Section: Introductionmentioning
confidence: 99%